2016
DOI: 10.1590/s0100-83582016340400006
|View full text |Cite
|
Sign up to set email alerts
|

Finding out Relationships Among Some Morpho-Biochemical Parameters of Christ's Thorn (Ziziphus spina-christi) under Drought and Salinity Stresses

Abstract: -Taking into consideration that modeling and indicating relationship among traits and variables are among the most useful numerical techniques in the biological and botanical researches, and also undeniable impact of drought and salinity stresses, this research was implemented with the aim to consider change in relationship among the traits under separately drought and salinity stresses related to scarcely distributed medicinal plant called Christ thorn (Ziziphus spina-christi). A glass house experiment was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…To prompt diverse aspect of association of several yield variables, different biometrical techniques have been developed. The PC analysis helps researchers to use simple illustrations such as factors loading to describe relationships among each variable under study [52,53]. In the present study, factor loading graph showed close association of yield with different morpho-biochemical and photosynthetic pigments.…”
Section: Plos Onesupporting
confidence: 55%
“…To prompt diverse aspect of association of several yield variables, different biometrical techniques have been developed. The PC analysis helps researchers to use simple illustrations such as factors loading to describe relationships among each variable under study [52,53]. In the present study, factor loading graph showed close association of yield with different morpho-biochemical and photosynthetic pigments.…”
Section: Plos Onesupporting
confidence: 55%
“…In previous studies, the first two PCs indicated to those relationships between the variables, which were interpreted as a related response to some of the soil variables by Islabão et al [24] as well as to some soil and plant variables by Juhos et al [25], Ferraz et al [26] and Gil et al [94]. PCA indicated that changes in the relationship between variables under different stresses are reasonable [72].…”
Section: Relationships Between the Soil And Plant Variablesmentioning
confidence: 87%
“…The water content % in plants is the most important physiological measure that affects the efficiency of photosynthesis, plant growth and biomass productivity, in addition to being an indicator of plant tolerance to drought and salinity, because water stress restricts transpiration, including stomata closure and water evaporation from the leaf surface [35]. Some chemical compositions such as K + and Na + revealed higher variation under salinity stress while some other chemical compositions like nitrogen showed higher variation under drought stress [72]. When stress intensity increases, the minerals uptake by the plant may decrease [73] and it was also found that some minerals in plants are reduced due to other minerals [21].…”
Section: Plant Analysismentioning
confidence: 99%
“…The plants were separated into shoots and roots and a part of the roots and fresh shoots were immediately frozen in liquid nitrogen for analysis. The dry weight of the plant was estimated by placing the samples in an oven at 60°C until obtaining a constant dry weight [ 63 ]. In addition, some of wheat were harvested at the ripening stage to record the yield component data, which included: plant height (cm), days to flowering, days to maturity, spike length (cm), grain yield (g plant -1 ), biological yield (g plant -1 ), weight of 100 grams (g), number of grains / spike [ 64 ].…”
Section: Methodsmentioning
confidence: 99%